2021
DOI: 10.3389/fpls.2021.660409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Stress on Growth, Physiological Parameters, and Ionic Concentration of Water Dropwort (Oenanthe javanica) Cultivars

Abstract: Salt stress is an important environmental limiting factor. Water dropwort (Oenanthe javanica) is an important vegetable in East Asia; however, its phenotypic and physiological response is poorly explored. For this purpose, 48 cultivars of water dropwort were grown hydroponically and treated with 0, 50, 100, and 200 mm NaCl for 14 days. Than their phenotypic responses were evaluated, afterward, physiological studies were carried out in selected sensitive and tolerant cultivars. In the present study, the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 67 publications
(130 reference statements)
15
101
0
Order By: Relevance
“…The activity of superoxide dismutase (SOD) was determined with SOD assay kit and was presented as U/gFW. One unit of SOD activity is the amount of extract that gives 50% inhibition in reducing xanthine monitored at 560nm ( Sunjeet et al, 2021 ). peroxidase (POD) activity was measured by using a POD assay kit based on the POD-catalyzed oxidation of a specific substrate by H 2 O 2 witvh characteristic light absorption at 470nm and expressed as U/gFW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of superoxide dismutase (SOD) was determined with SOD assay kit and was presented as U/gFW. One unit of SOD activity is the amount of extract that gives 50% inhibition in reducing xanthine monitored at 560nm ( Sunjeet et al, 2021 ). peroxidase (POD) activity was measured by using a POD assay kit based on the POD-catalyzed oxidation of a specific substrate by H 2 O 2 witvh characteristic light absorption at 470nm and expressed as U/gFW.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the activity of CAT was measured with a CAT assay kit and was presented as U/gFW. One unit of CAT activity is the amount of enzyme which causes the decomposition of 1μmol H 2 O 2 per minute in 1mg fresh sample at 37°C ( Sunjeet et al, 2021 ). The glutathione reductase (GSH) content was determined with a glutathione assay kit according to the DTNB [5, 5, − dithiobis (2-nitrobenzoic acid)] method.…”
Section: Methodsmentioning
confidence: 99%
“…From that context, indifferent H 2 O 2 accumulation between Ca and Ca+BR after 5 days of stress cannot be conducive to the inefficacy of BR treatment in minimizing ROS. In the study on water dropwort, it was found that stress conditions could promote the accumulation of Pro and soluble sugar in plants ( Kumar et al, 2021 ). However, the effects of exogenous BR on Pro accumulation under stress were inconsistent in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic stress occurs as a result of the excessive concentration of salts, decreased water potential and plants' inability to uptake water. Consequently, this leads to an ion imbalance in the plants and accumulation of salts ions in plant tissues [68,69]. This can contribute to heavy damage to plant metabolisms, which can further lead to stunted plant growth and reduced yield [65].…”
Section: Salinizationmentioning
confidence: 99%